Evidence-Based Cosmology — Black Holes as Rejuvenating Systems of the Universe - Amrit Srečko Šorli; Saeid Jafari; Davide Fiscaletti; Rado Gorjup; Niko Gorjup; Tomaž Makovec (Reports in Advances of Physical Sciences, 2023)
Evidence-based cosmology (EBC) is a cosmological model that has no theoretical presumptions. In EBC, every element in the model has a corresponding element in physical reality that is observed and measured. The EBC is related to the real observable universe by a bijective function of set theory. Supermassive black holes (SMBH) in the centers of galaxies are rejuvenating systems of the universe. In the center of SMBH energy density of superfluid space is so low that atoms become unstable and fall apart into elementary particles. SMBHs transform old matter into fresh energy in the form of jets that are composed of elementary particles. This transformation of old matter into fresh energy is permanent. It has no beginning and it will not have an end. Rotation of SMBHs is rotating local superfluid space which is the physical origin of galactic rotation curves.